Remarkably distinct mechanical flexibility in three structurally similar semiconducting organic crystals studied by nanoindentation and molecular dynamics - Devarapalli, Ramesh; Kadambi, Sourabh Bhagwan; Chen, Chun-Teh; Krishna, Gamidi Rama; Kammari, Bal Raju; Buehler, Markus J.; Ramamurty, Upadrasta; Reddy, C. Malla (Chemistry of Materials, 2019)
Distinct macroscopic mechanical responses of the three crystals of naphthalene diimide derivatives, 1Me, 1Et, and 1nPr, studied here are very intriguing because their molecular structures are very similar, with the difference only in the alkyl chain length. Among the three crystals examined, 1Me shows highly plastic bending nature, 1Et shows elastic flexibility, and 1nPr is brittle. A detailed investigation by nanoindentation and molecular dynamics (MD) simulations allowed us to correlate their distinct mechanical responses with the way the weak interactions pack in crystal structures. The elastic modulus (E) of 1Me is nearly an order of magnitude lower than that of 1Et, whereas hardness (H) is less than half. The low values of E and H of 1Me indicate that these crystals are highly compliant and offer a low resistance to plastic flow. As the knowledge of hardness and elastic modulus of molecular crystals alone is insufficient to capture their macroscopic mechanical deformation nature, that is, elastic, brittle, or plastic, we have employed three-point bending tests using the nanoindentation technique. This allowed a quantitative evaluation of flexibility of the three mechanically distinct semiconducting molecular crystals, which is important for designing larger-scale applications; these were complemented with detailed MD simulations. The elastic 1Et crystals showed remarkable flexibility even after 1000 cycles. The results emphasize that the alkyl side chains in functional organic crystals may be exploited for tuning their self-assembly as well as their mechanical properties. Hence, the study has broad implications, for example, in crystal engineering of various flexible, ordered molecular materials.

Green catalyst Fe(OTs)(3)/SiO2 for the synthesis of 4-Pyrrolo-12-oxoquinazolines - Allaka, Bhargava Sai; Basavoju, Srinivas; Krishna, Gamidi Rama (ChemistrySelect, 2020)
An efficient and eco-friendly diversity-oriented synthetic protocol has been presented to synthesize structurally versatile drug-like molecules under solvent-free grinding in the presence of Fe(OTs)(3)/SiO2 as a catalyst. The use of Fe(OTs)(3)/SiO2 as a recyclable and reusable catalyst has been explored in the synthetic domino protocol involving one-pot, three component reaction for the synthesis of 4-pyrrolo-12-oxoquinazolines with special features of the protocol like high atom-economy, operational simplicity, short reaction time and high selectivity with excellent yields.
Keywords: 4-Pyrrolo-12-oxoquinazolines; Fe(OTs)(3); Green methodology; Liquid Assisted Grinding (LAG); SiO2 catalyst; Solvent-free grinding

Pd-catalyzed annulation of beta-iodovinyl sulfones with 2-halophenols: a general route for the synthesis of 3-sulfonyl benzofuran derivatives - Reddy, Raju Jannapu; Kumar, Jangam Jagadesh; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2020)
The palladium-catalyzed annulation between beta-iodovinyl sulfones and 2-halophenols or 1-bromo-2-naphthol or 2-bromo-3-pyridinol is presented. The annulation process involving oxa-Michael addition-elimination and intramolecular Heck reaction leading to form 2,3-disubstituted benzofurans (aryl benzofuryl sulfones) in good to high yields. The regioselective tandem construction of C-O and C-C bonds has been achieved with a variety of substitution patterns. Moreover, the tandem process is reliable at gram-scale reactions and a plausible mechanism is also proposed.
Keywords: Benzofurans; beta-Iodovinyl sulfones; Heck reaction; Naphthofurans; oxa-Michael addition

Phenylboronic acid-catalyzed tandem construction of S-S and C-S bonds: a new method for the synthesis of benzyl disulfanylsulfone derivatives from S-benzyl thiosulfonates - Reddy, Raju Jannapu; Waheed, Md; Krishna, Gamidi Rama (Organic & Biomolecular Chemistry, 2020)
A unique phenylboronic acid-catalyzed dimerization-sulfonylation of S-benzyl thiosulfonates has been disclosed. A metal-free tandem construction of S-S and C-S bonds is an operationally simple method to access a wide range of benzyl disulfanylsulfone derivatives in high to excellent yields. Moreover, the robustness of this tandem transformation has been demonstrated by gram-scale reactions, and a plausible mechanism is also proposed.

Total synthesis and absolute configuration determination of Ktedonoketone, a benzenoid metabolite from Thermophilic bacterium - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Tetrahedron Letters, 2020)
The successful total synthesis of both enantiomers of ktedonoketone allowed us to decipher an unambiguous assignment of absolute configuration of the natural product. The concise synthesis highlights Wacker oxidation and aldol condensation as key steps. In addition to this, the current synthetic route is suitable to access a library of compounds on the similar skeleton as one can use readily available amino acids and Grignard reagents as variants. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Absolute configuration; Ktedonoketone; Total synthesis; Wacker oxidation

Nickel-catalyzed difunctionalization of alkynyl bromides with thiosulfonates and N-arylthio succinimides: a convenient synthesis of 1,2-thiosulfonylethenes and 1,1-dithioethenes - Kumari, Arram Haritha; Kumar, Jangam Jagadesh; Krishna, Gamidi Rama; Reddy, Raju Jannapu (Synthesis-Stuttgart, 2021)
An efficient nickel-catalyzed vicinal thiosulfonylation of 1bromoalkynes with thiosulfonates in the presence of cesium carbonate is described. An operationally simple and highly regioselective atom transfer radical addition (ATRA) of alkynyl bromides provides a wide range of (E)-1,2-thiosulfonylethenes (alpha-aryl-beta-thioarylvinyl sulfones) in moderate to high yields. The extensive substrate scope of both alkynyl bromides and thiosulfonates is explored with a broad range of functional groups. Indole-derived 1,1- bromoalkenes were also successfully explored in this 1,2-thiosulfonylation process. Moreover, the nickel-catalyzed geminal- dithiolation of alkynyl bromides with N-arylthio succinimides provides 1,1-dithioalkenes in high yields. The present protocol is reliable on gram scale, and a sequential one-pot bromination and thiosulfonylation of phenylacetylene is achieved in a scale-up synthesis. Following control experiments, a plausible mechanism is proposed to rationalize the experimental outcome and the vicinal thiosulfonylation.
Keywords: alkynyl bromides; atom transfer radical addition (ATRA); thiosulfonates; thiosulfonylation; vinyl thiosulfones

Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.

Tuning of alpha-silyl carbocation reactivity into enone transposition: application to the synthesis of peribysin D, E-volkendousin, and E-guggulsterone - Athawale, Paresh R.; Zade, Vishal M.; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Organic Letters, 2021)
A reliable method for enone transposition has been developed with the help of silyl group masking. Enantio-switching, substituent shuffling, and Z-selectivity are the highlights of the method. The developed method was applied for the first total synthesis of peribysin D along with its structural revision. Formal synthesis of E-guggulsterone and E-volkendousin was also claimed using a short sequence.

Diethyl phosphite-mediated switchable synthesis of bis(imidazoheterocycles) derived disulfanes and sulfanes using imidazoheterocycles and octasulfur - Reddy, Raju Jannapu; Shankar, Angothu; Kumar, Jangam Jagadesh; Sharadha, Nunavath; Krishna, Gamidi Rama (New Journal of Chemistry, 2022)
A practical and highly efficient oxidative dual C-H sulfenylation of imidazoheterocycles using odorless, inexpensive elemental sulfur in DMSO to synthesize sulfur-bridged imidazoheterocycles under metal-free conditions is reported. The amount of diethyl phosphite and sulfur powder most attractively permits a tunable synthesis of bis(imidazoheterocycle)disulfanes and bis(imidazoheterocycle)sulfanes in good to high yields. A comprehensive substrate scope with a broad range of functional group tolerance was realized, and the efficacy of the process was proved at gram-scale reactions. Next, the bis(imidazopyridine)disulfanes were smoothly reacted with various indoles under similar conditions to form the corresponding imidazo[1,2-a]pyridine-indole-derived thioethers in high yields. A plausible mechanism has been proposed based on the control experiments.

Interrupted CuAAC-thiolation for the construction of 1,2,3-triazole-fused eight-membered heterocycles from O-/N-propargyl derived benzyl thiosulfonates with organic azides - Reddy, Raju Jannapu; Waheed, Md; Kumari, Arram Haritha; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2022)
A copper(I)-catalyzed interrupted click-sulfenylation of O-/N-propargyl benzyl thiosulfonates with organic azides has been disclosed. The unified CuAAC-thiolation provides a wide range of triazole-fused eight-membered heterocycles in good to high (51-94%) yields under mild reaction conditions. Moreover, a three-component reaction is also achieved involving O-/N-propargyl benzyl thiosulfonates, benzyl bromide, and sodium azide to deliver fused-triazoles in 61-74% yields. From a synthetic point of view, the present protocol has been demonstrated at gram-scale reactions. A plausible mechanism is also proposed based on experimental results and control experiments.
Keywords: Eight-Membered Heterocycles; Fused-Triazoles; Interrupted-Click Reaction; Thiolation; thiosulfonates

K3PO4-promoted cycloannulation of (E)-beta-Iodovinyl Sulfones with ortho-Hydroxy-chalcones/cinnamates for the synthesis of 2,3,4-trisubstituted 4h-benzopyran derivatives - Reddy, Raju Jannapu; Kumar, Jangam Jagadesh; Krishna, Gamidi Rama (Advanced Synthesis & Catalysis, 2022)
K3PO4-mediated cycloannulation of (E)-beta-iodovinyl sulfones with ortho-hydroxy chalcones/ortho-hydroxy cinnamates has been realized to access 2,3,4-trisubstituted-4H-benzopyran derivatives. A metal-free tandem oxa-Michael addition and cycloannulation allows the diversity-oriented synthesis of the corresponding 3-sulfonyl-4H-benzopyrans in good to high yields. More importantly, one-pot three-component reaction between (E)-beta-iodovinyl sulfones, 2-hydroxybenzaldehydes, and phosphonium ylides has been established for the synthesis of 4H-chromene derivatives in moderate to good yields. Notably, this metal-free process features a broad substrate scope and easy elaboration into numerous multifaceted chromene products, including bioactive estrone-derivative. The present protocol is sustainable at the gram scale reactions, and post-synthetic applications were also demonstrated. A plausible mechanism is also presented on the basis of existing experimental results.
Keywords: (E)-beta-Iodovinyl sulfones; Benzopyrans; Cycloannulation; ortho-Hydroxy Chalcones; Sulfones

Novel pharmaceutical cocrystal of apalutamide, a nonsteroidal antiandrogen drug: synthesis, crystal structure, dissolution, stress, and excipient compatibility - Saladi, Venkata Narasayya; Kammari, Bal Raju; Mandad, Pratap Reddy; Krishna, Gamidi Rama; Sajja, Eswaraiah; Thirumali, Rajan S.; Marutapilli, Arthanareeswari; Mathad, Vijayavitthal T. (Crystal Growth & Design, 2022)
Apalutamide (APA), a second-generation nonsteroidal antiandrogen BCS Class II drug with poor solubility and high permeability. A novel 1:1 cocrystal of Apalutamide (APA) with methylparaben (MP) was identified by cooling crystallization during the cocrystal screening and characterized by various solid-state techniques, such as PXRD, DSC, TGA, FT-IR, and 13C solid-state CP-MAS NMR spectroscopy. The crystal structures of APA and its cocrystal (APA-MP) were determined by the SC-XRD technique. The crystal structure analysis of the APA-MP cocrystal revealed that the APA and MP molecules are connected through strong O–H···O hydrogen bonds. The novel cocrystal improves the solubility and dissolution rate in different physiological conditions compared to poorly soluble APA due to strong hydrogen bond between the drug and the coformer. The cocrystal is stable (physically and chemically) under stress conditions, such as exposure to the relative humidity, mechanical grinding, open exposure to atmosphere at cRT (critical room temperature) and compression pressure of 10 tons. In addition, the compatibility of the cocrystal with excipients used in the drug product of APA (ERLEADA) was also investigated, and no disproportionation of cocrystal was observed.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Solvent-driven mono- and bis-sulfenylation of (E)-beta-iodovinyl sulfones with thiols for flexible synthesis of 1,2-thiosulfonylalkenes and 1,2-dithioalkenes - Reddy, Raju Jannapu; Kumari, Arram Haritha; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2022)
The nature of solvent is a key factor for stereoselective mono-and bis-thiolation of (E)-beta-iodovinyl sulfones with thiols under basic conditions. A novel and unprecedented vicinal bisthiolation of (E)-beta-iodovinyl sulfones with thiols under the influence of K2CO3/DMSO at room temperature for quick assembly of (E)-1,2-dithio-1-alkenes is presented. Solvent-induced stereoselective monosulfenylation of (E)-beta-iodovinyl sulfones with thiols has also been established for the synthesis of both (E)- and (Z)-1,2-thiosulfonylethenes in MeCN and MeOH, respectively. Moreover, K2CO3-mediated desulfonylative-sulfenylation of (Z)-1,2-thiosulfonylethenes with thiols in DMSO furnished unsymmetrical (Z)-1,2-dithio-1-alkenes for the first time. The solvent-dependent versatile reactivity of (E)-beta-iodovinyl sulfones has been successfully explored to provide a set of (E)-/(Z)-1,2-dithio-1-alkenes and (E)-/(Z)-1,2-thiosulfonyl-1-alkenes in good to high yields with excellent stereoselectivities. Notably, this operationally simple process utilizes a broad substrate scope with good functional group tolerance and compatibility. The efficacy of the process has been proven for gram-scale reactions, and plausible mechanistic models are outlined on the basis of experimental results and control experiments.

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction

Carbamate-Protected (BOC and O-NB) 2-Aminopyrimidinedione-based janus G-C nucleobase motifs as building blocks for supramolecular assembly and smart polymers - Singh, Dharmendra; Lakshmi, Durga; Meena, Chhuttan L.; Krishna, Gamidi Rama; Sanjayan, Gangadhar J. (Journal of organic chemistry, 2023)
In this paper, we report ``carbamate protected'' 2-aminopyrimidinedione-based Janus G-C nucleobases (2-APD Janus G-C nucleobases) featuring polymerizable groups and self-complementary triple H-bonding motifs DDA and AAD as building blocks for developing smart polymers and self-healing materials. The carbamate-masked H-bonding motif, cleavable under acidic (BOC group) or photocleavable (O-nitrobenzyl group) conditions, would facilitate the synthesis of smart polymers by alleviating aggregation during polymerization which in turn would exclude self-assembly-assisted solubility issues. Ready accessibility in excellent yields coupled with the possibility for facile introduction of polymerizable groups would make these building blocks excellent candidates for diverse polymerization applications.

Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication

Origin of optoelectronic contradictions in 3,4-cycloalkyl[c]-chalcogenophenes: a computational study - Masilamani, Ganesh; Krishna, Gamidi Rama; Debnath, Sashi; Bedi, Anjan (Polymers, 2023)
The planar morphology of the backbone significantly contributes to the subtle optoelectronic features of pi-conjugated polymers. On the other hand, the atomistic tuning of an otherwise identical pi-backbone could also impact optoelectronic properties systematically. In this manuscript, we compare a series of 3,4-cycloalkylchalcogenophenes by tuning them atomistically using group-16 elements. Additionally, the effect of systematically extending these building blocks in the form of oligomers and polymers is studied. The size of the 3,4-substitution affected the morphology of the oligomers. In addition, the heteroatoms contributed to a further alteration in their geometry and resultant optoelectronic properties. The chalcogenophenes, containing smaller 3,4-cycloalkanes, resulted in lower bandgap oligomers or polymers compared to those with larger 3,4-cycloalkanes. Natural bonding orbital (NBO) calculations were performed to understand the disparity alongside the contour maps of frontier molecular orbitals (FMO).
Keywords: chalcogenophene; DFT calculation; Morphology; optoelectronic properties; steric effect

Pd(II)-catalyzed tandem cycloannulative-alkenylation of o-alkynyl-phenols/anilines with (E)-β-Iodovinyl sulfones: a direct strategy to construct 3-(Vinyl sulfonyl)benzoheterole derivatives - Reddy, Raju Jannapu; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2023)
Benzoheterolesand vinyl sulfones are the most promisingpharmaceuticalrelevance motifs, yet the hybrid analogues of these scaffolds stillneed to be explored. We report herein a general and highly efficientPd(OAc)(2)-catalyzed intramolecular cyclization and vinylationof o-alkynylphenols/o-alkynylanilineswith (E)-beta-iodovinyl sulfones under mild reactionconditions. A direct C(sp(2))-C(sp(2)) cross-couplingis enabled for the diversity-oriented synthesis of vinyl sulfone-tetheredbenzofurans and indoles in good to high yields with excellent stereoselectivity.Notably, this tandem process was consistent at the gram scale, andin situ, generation of 2-(phenylethynyl)phenol has also been utilizedin a scalable synthesis. Late-stage synthetic transformations werealso further explored, including isomerization and desulfonylative-sulfenylation.Moreover, several control experiments were accomplished, and we proposeda plausible mechanism based on existing experimental results.

Radical cascade cyclization of unactivated alkene-tethered indoles with aryldiazonium salt and sodium metabisulfite to access Azo- and Sulfonylated-2,3-Dihyro-1H-pyrrolo[1,2-a]indoles - Kumar, Pawan; Rai, Archana; Kumar, Manish; Krishna, Gamidi Rama; Das, Utpal (Journal of Organic Chemistry, 2023)
A method for the construction ofheterocyclic scaffold2,3-dihyro-1H-pyrrolo[1,2-a]indolesvia arylsulfonylradical-triggered cascade cyclization of unactivated alkene-tetheredindoles in the absence of any external photocatalyst has been developed.This protocol features easily accessible starting materials such assodium metabisulfite and aryldiazonium tetrafluoroborates at roomtemperature and offers good functional group compatibility, enablingthe introduction of various functionalized sulfonyl and azo groupsinto pyrrolo[1,2-a]indoles.

Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies

Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.

Total synthesis and absolute configuration determination of the α-glycosidase inhibitor (3S,4R)-6-Acetyl-3-hydroxy-2,2-dimethylchroman-4-yl (Z)-2-Methylbut-2-enoate from Ageratina grandifolia - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Journal of Natural Products, 2023)
Herein, we report the first total synthesis of & alpha;-glycosidaseinhibitor (3R, 4S)-6-acetyl-3-hydroxy-2,2-dimethylchroman-4-yl(Z)-2-methylbut-2-enoate as well as its enantiomer.Our synthesis confirms the chromane structure separately proposedby Navarro-Vazquez and Mata, on the basis of DFT computations. Furthermore,our synthesis allowed us to determine the absolute configuration ofthe natural compound as (3S, 4R)and not (3R, 4S).

Ultrasound assisted synthesis of spirooxindolo-1,2,4-oxadiazoles via [3+2] cycloaddition reaction and their anti-cancer activity - Kanchrana, Madhu; Allaka, Bhargava Sai; Krishna, Gamidi Rama; Basavoju, Srinivas (ARKIVOC, 2023)

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.

Ionic liquid assisted green synthesis of quinoxaline based bisspirooxindoles: anticancer evaluation and molecular dynamics - Kanchrana, Madhu; Krishna, Gamidi Rama; Dey, Biswajit; Pandey, Nandita; Guru, Santosh Kumar; Sangolkar, Akanksha Ashok; Pawar, Ravinder; Basavoju, Srinivas (CHEMISTRYSELECT, 2024)
Keywords: Cycloaddition; spirooxindoles

Metal-free one-pot domino synthesis of oxazolidinethione derivatives of quaternary amino acids from α-amino esters and aldehydes using CS2 - Shinde, Dinesh R.; Krishna, Gamidi Rama; Marelli, Udaya Kiran (Journal of Organic Chemistry, 2024)
We present a streamlined, metal-free, one-pot domino approach to efficiently synthesize oxazolidinethione derivatives containing substituted quaternary amino acids. This method employs alpha-amino esters, aldehydes, and CS2 under mild conditions, constructing three new bonds (C-N, C-C, and C-O) to produce oxazolidinethione compounds featuring a quaternary center and a beta-hydroxy derivative in high yields. This scalable protocol enables the creation of libraries of biologically significant, intricate amino acid derivatives using amino esters and aldehydes.

Novel molecular adducts of an anti-cancer drug vandetanib with enhanced solubility - Bandaru, Ravi Kumar; Giri, Lopamudra; Krishna, Gamidi Rama; Dandela, Rambabu (Crystengcomm, 2024)
The solubility, permeability, and dissolution rate of an active pharmaceutical ingredient (API) are critical factors in determining its pharmacokinetic performance in oral dosage forms. Modifying these properties can potentially enhance the drug's pharmacokinetics. Vandetanib (VDTB), classified as a class II anti-cancer drug in the biopharmaceutical classification system (BCS), suffers from low solubility (0.008 mg mL-1) and an extended pharmacokinetic half-life (19 days), necessitating the administration of high doses, which leads to undesirable side effects. To address this issue, we have employed a crystal engineering approach to enhance the solubility of VDTB. We employed the liquid-assisted grinding (LAG) method followed by the slow evaporation technique to prepare novel solid forms of VDTB by incorporating various aliphatic dicarboxylic acids, including succinic acid (SUA), adipic acid (ADA), pimelic acid (PIA), azelaic acid (AZA), and sebacic acid (SBA). These newly obtained solid forms were characterized by SC-XRD, PXRD, TGA, and DSC experiments. The crystal structure analyses revealed a proton transfer between the carboxylic acid group of aliphatic acids and the N-methyl piperidine moiety of VDTB, confirming salt/adduct formation. Additionally, all of the molecular salts were stabilized by charge-assisted N+-HMIDLINE HORIZONTAL ELLIPSISO- hydrogen bonds, while the parent VDTB crystal structure is stabilised by N-HMIDLINE HORIZONTAL ELLIPSISN interactions. Moreover, the solubility and dissolution rate of these new solid forms were assessed in a pH 7.4 phosphate buffer medium, with the results indicating that all of the solid forms, except for VDTB:SBA, exhibited higher solubility compared to pure VDTB. These findings offer promising prospects for the development of an improved VDTB formulation with enhanced pharmacokinetic properties. Successful attempt to improve the solubility and dissolution rate of Vandetanib - an anti-cancer drug, by crystal engineering approach.
Keywords: Amorfization; hydrate; Parameters; Salt; Thyroid-Cancer

One-pot synthesis of pyrazoles from sulfonyl hydrazides and alkynyl ketones using environmentally benign sulfonium iodate (I) reagent - Mishra, Akanksha; Talukdar, Mrinal; Krishna, Gamidi Rama; Begari, Eeshwaraiah (ChemistrySelect, 2024)
Pyrazole is an omnipresent moiety in many natural products and pharmaceutically active compounds. Here, we have developed a simple and dynamic method for one-pot synthesis of substituted pyrazoles through the intramolecular cyclization of hydrazides and alkynyl ketones, using a novel sulfonium saltbased iodate (& Iukcy;) reagent system. This method has the advantage that it proceeds in a one-pot, without isolating a less stable hydrazone intermediate. Hypervalent iodine-based reagents are an environmentally benign and greener option to toxic metal oxidants; they have an extensive application in metal-catalyst-free reactions, and this reaction proceeds in less time with high yields.
Keywords: Deprotonation; One-pot reaction; Oxidative iodination; Pyrazole; S(N)2-type cyclization

Organocatalyzed [4+2] cycloaddition of α,β-unsaturated ketones and isatylidene malononitrile: accessing spiro[3-arylcyclohexanone]oxindole derivatives - Patil, Baliram R.; Nichinde, Chandrakant B.; Chaudhari, Suryakant S.; Krishna, Gamidi Rama; Kinage, Anil K. (RSC Advances, 2024)
Herein, we developed a series of compounds featuring spiro[3-arylcyclohexanone]oxindoles through Barbas [4 + 2] cycloaddition reactions between isatylidene malononitrile and alpha,beta-unsaturated ketones using l-proline as an organocatalyst. The reported methodology offers many advantages such as mild reaction conditions, diverse substrate scope with high yields, easy reaction setup, and use of easily synthesizable starting materials. An l-proline catalyzed-Barbas-[4 + 2]-cycloaddition reaction is reported for the synthesis of spiro[3-arylcyclohexanone]oxindole derivatives. The method can tolerate a diverse substrate scope with high yields.

Transfer semi-hydrogenation of terminal alkynes with a well-defined iron complex - Chowdhury, Deep; Goswami, Souvik; Krishna, Gamidi Rama; Mukherjee, Arup (Dalton Transaction, 2024)
The synthesis and characterization of a bis-iron(ii) complex was accomplished upon treatment of a phosphine free NNN-pincer ligand (L) with FeCl2 center dot 4H2O under ambient conditions. The deep greenish colored iron(ii) complex (Fe-1) was characterized by a single-crystal X-ray diffraction study along with IR spectroscopy, UV-Vis spectroscopy, mass spectrometry, and elemental analysis. The Fe-1 complex was tested for the transfer semi-hydrogenation of terminal alkynes to the corresponding alkenes through the dehydrogenation of dimethyl amine-borane. This procedure enables the conversion of various structurally different terminal alkynes to alkenes under mild conditions. Control experiments were performed to shed light on the possible intermediates generated during the present protocol. A bench stable iron(ii) complex with the pincer ligand backbone was synthesized and characterized. The well-defined iron complex was successfully utilized for the dehydrogenation of DMAB and subsequent transfer semi-hydrogenation of terminal alkynes.

AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols and aldehydes: enabling the diastereoselective synthesis of [6,6,6]-trioxa-fused ketals and hexahydro-2H-chromenes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2025)
We report the unprecedented diastereoselective synthesis of novel [6,6,6]-trioxa-fused ketals via AgOTf-catalyzed cascade annulation of 5-hexyn-1-ols (with primary or secondary hydroxyl groups) and aldehydes through a [2+2+1+1] pathway. In contrast, 5-hexyn-1-ols with tertiary hydroxyl groups yield hexahydro-2H-chromenes via a [3+1+1+1] pathway.

Base mediated approach for the synthesis of deoxybenzoins using γ-aryl-β-ketoesters and benzoyl chlorides - Choudhary, Shailendra Singh; Darole, Ratanamala S.; Krishna, Gamidi Rama; Senthilkumar, Beeran (RSC Advances, 2025)
This study introduces a one-pot, transition metal-free strategy for synthesizing deoxybenzoins, overcoming the challenges of conventional methods. The reaction involves dual acylation of gamma-aryl beta-keto esters using K2CO3 in dioxane at 90 degrees C, followed by a concerted transformation to form deoxybenzoin. The protocol operates under mild conditions, tolerates a broad range of substrates, and produces minimal by-products, making it a practical, scalable alternative for accessing pharmaceutically relevant deoxybenzoins.

Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate

Phytochemical investigation of Cannabis sativa: Isolation and structure determination of spiroindans - Nalli, Yedukondalu; Komal; Boccia, Eleonora; Lauro, Gianluigi; Bifulco, Giuseppe; Krishna, Gamidi Rama (Journal of Molecular Structure, 2025)
Four undescribed, beta-, alpha-chevicospiranol (1, 2), 4-prenylspirenone B (3), and, 6-prenylspirenone B (4), along with ten known spiroindans were discovered in Cannabis sativa. The structures were determined through 1D, 2D NMR, HRMS, and quantum mechanical calculations. Compounds 1 and 2 have an unprecedented fused system of 3hydroxychavicol with beta- and alpha-cannabispiranol core, respectively, while 3 and 4 are prenylated spiroindan congeners. Detailed NMR data assignments of isomeric pairs 2a - 2b, 3a - 3b, and 4a - 4b, corrected the misidentification of the previously reported spiroindane, prenylspirodinone (5). Besides, the crystal structures of 2a, 3a, and 5a were determined by SC-XRD experiments.
Keywords: Cannabaceae; Cannabis sativa L.; Crystal structure analysis of spiro-indans; Indian cannabis variety; NMR data of spiro-indans; Spiro-indans